Business in a changing society : Festschrift for Peter Braeck-Letmathe - Koopmann, Andreas, ....- (Zürich : Neue Zurcher Zeitung, 2014)
On the occasion of Peter Brabeck-Letmathe's 70th birthday a group of his friends invited 31 authors to contribute to this festschrift, honoring his great achievements in providing business leadership and contributing to public dialogue on important issues. Leaders from politics, academia, civil society and business who know Peter Brabekc draw a fascinating, multifaceted picture of the quality, speed and nature of the ongoing and often accelerating change taking place in society, technology and markets. It is a change that is not only relevant for him as chairman of Nestlé, but also for citizens and businesses around the world today, and in years to come.
Keywords: Handel -- Internationale handel; Multinationale ondernemingen